2023
DOI: 10.1108/ijshe-08-2023-0368
|View full text |Cite
|
Sign up to set email alerts
|

Predicting food waste reduction behavior among students in higher education institutions

Alvin Patrick Valentin,
Aivanne Miguel Dela Vega,
Marc Ivenson Kho
et al.

Abstract: Purpose This study aims to determine and analyze the predictors of food waste reduction intention and behavior among higher education institutions (HEIs) using an extended version of the theory of planned behavior (TPB). Design/methodology/approach This study empirically tested an extended TPB model through regression analyses using data obtained through an online survey. Findings Attitude toward food waste reduction, subjective norms, perceived behavioral control and food waste knowledge predicted intenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 40 publications
3
6
0
Order By: Relevance
“…People's attitudes towards reducing waste can be influenced by various factors, such as personal norms, knowledge about waste minimization [33], perceived benefits [49], and awareness of consequences [13]. Previous studies have found that attitudes play an important role in intentions to reduce waste of food [31,32,49,50], energy [30], construction materials [33,51], and water [9,52]. Additionally, attitudes have been shown to be a significant predictor of farmers' intentions to recycle farming water waste [11], and tourists' attitudes have been found to predict their intentions to reduce waste as well [53].…”
Section: Attitudesmentioning
confidence: 99%
See 4 more Smart Citations
“…People's attitudes towards reducing waste can be influenced by various factors, such as personal norms, knowledge about waste minimization [33], perceived benefits [49], and awareness of consequences [13]. Previous studies have found that attitudes play an important role in intentions to reduce waste of food [31,32,49,50], energy [30], construction materials [33,51], and water [9,52]. Additionally, attitudes have been shown to be a significant predictor of farmers' intentions to recycle farming water waste [11], and tourists' attitudes have been found to predict their intentions to reduce waste as well [53].…”
Section: Attitudesmentioning
confidence: 99%
“…Skevas et al [55] found that peer groups play a significant role in shaping farmers' adoption of new technologies like unmanned aerial vehicles. Previous studies have also shown that perceived social pressure can positively influence intentions to reduce waste [32][33][34]50,53] and conserve water [4,36,45,47,52]. For their part, Rasoulkhani et al [1] noted that word of mouth, through social network interactions, may stimulate intentions to adopt water conservation technology.…”
Section: Social Influencementioning
confidence: 99%
See 3 more Smart Citations